2009
DOI: 10.3390/ma2041558
|View full text |Cite
|
Sign up to set email alerts
|

Organotin Polyethers as Biomaterials

Abstract: Organotin polyethers are easily synthesized employing interfacial polymerization systems involving the reaction of hydroxyl-containing Lewis bases and organotin halides. A wide variety of organotin-containing polymeric products have been synthesized including those derived from natural and synthetic polymers such as lignin, xylan, cellulose, dextran, and poly(vinyl alcohol). Others have been synthesized employing known drug diols such as dicumarol, DES, and dienestrol and a wide variety of synthetic diols. Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 96 publications
(194 reference statements)
2
31
0
2
Order By: Relevance
“…We also find that the active agent is the polymer and not the degradation products [26]. This is consistent with studies that show that the polymers are stable in DMSO with half-chain lives, the time for the chain length to halve, generally in excess of 30 weeks [6][7][8][9]. In Use of metal-containing polymers as potential anticancer agents…”
Section: Metal-containing Polymers As Anticancer Agentssupporting
confidence: 89%
See 2 more Smart Citations
“…We also find that the active agent is the polymer and not the degradation products [26]. This is consistent with studies that show that the polymers are stable in DMSO with half-chain lives, the time for the chain length to halve, generally in excess of 30 weeks [6][7][8][9]. In Use of metal-containing polymers as potential anticancer agents…”
Section: Metal-containing Polymers As Anticancer Agentssupporting
confidence: 89%
“…For instance, polymers from organotin ( Figure 1) and metallocene ( Figure 3,4) exhibit good ability to inhibit cancer cell lines. In fact, the hafnocene and zirconocene products show EC 50 values in the other studies the polymers are found to be cytotoxic and cell death is by necrosis [6][7][8]. Most organometallic compounds associate with polar solvents such as DMSO and the biological results may be influenced by the presence of the DMSO [27][28][29].…”
Section: Water-soluble Polymers Futurementioning
confidence: 83%
See 1 more Smart Citation
“…Our approach is to select Lewis bases that themselves have some biological activity, not necessarily anticancer, in hopes that the combination will have a synergetic effect. All of the Group 4 metallocene dichlorides exhibit anticancer activity [18][19][20][21][22]. In fact, only two metal-containing molecules have undergone human cancer treatment.…”
Section: Treatment Of Cancermentioning
confidence: 99%
“…High performance organometallic polymers which can offer properties like electronic, photonic and biomedical have drawn much attention in the field of polymer science and engineering (Carraher et al, 1979;Carraher and Roner, 2009). Metal incorporation is an important synthetic approach which can modify its surface and biological activity or provide sites for further modifications to improve the biocompatibility of organic compounds.…”
Section: Introductionmentioning
confidence: 99%